Macro and molecular level insights on gas hydrate growth in the presence of hofmeister salts - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2020)
The effect of few monovalent salts (NaCl, NH4Cl, and GdmCl) as additives, according to the Hofrneister series on the growth of methane gas hydrates, has been studied using experiments as well as molecular dynamics (MD) simulation. Further, the Hofmeister effects on hydrate crystallization have been correlated with the methanol as an additive, which is a known thermodynamic hydrate inhibitor for hydrate growth. One of the previous studies (discussed later in this article) available in the literature concludes that methane hydrate formation from ice might show enhanced kinetics in the presence of salts; this behavior is contrary to the general usage of such salts as hydrate inhibitors. This conclusion may not necessarily be true for experiments done with liquid water, and therefore, this work explores the behavior of these salts in a lab-scale setup. In addition, current work reports detailed MD simulation studies to gain insight into the mechanism of hydrate formation in the presence of Hofmeister series salts at two different concentrations of 1 and 10 wt % in water and compare the results with hydrate formation in the methanol-water system. Our study suggests that the presence of these additives at low concentrations (1 wt %) does enhance the hydrate growth kinetics. However, at higher concentrations (10 wt %), inhibition by these additives persisted, and prolonged nucleation, as well as retarded growth, was observed.